O-180 Oocyte vitrification for fertility preservation does not delay the initiation of neoadjuvant chemotherapy for breast cancer. (6th August 2021) - Sellami, I; Grynberg, M; Benoit, A; Sifer, C; Mayeur, A; Sonigo, C
Abstract: Study question: Does oocyte vitrification for fertility preservation (FP) delay the initiation of neoadjuvant chemotherapy for breast cancer? Summary answer: The indication of neoadjuvant chemotherapy for breast cancer should not be considered as an impediment to urgent oocyte vitrification for FP. What is known already: FP is considered as one of the most important issues to address for young breast cancer patients. Cryopreservation of oocytes or embryos may be considered after controlled ovarian hyperstimulation (COH) or in vitro maturation (IVM). Pregnancies have been reported after reutilization of oocytes frozen following both procedures. Although oocyte competence is better after COH, this strategy requires on average 13 days to be achieved. In addition, the safety of ovarian stimulation before tumor removal is currently not formally established. In case of neoadjuvant chemotherapy, the risk-benefit balance of COH is not well known. Study design, size, duration: Retrospective cohort study including all breast cancer patients eligible for oocyte vitrification following COH or IVM before initiation of neoadjuvant chemotherapy between January 2016 and December 2020. Participants/materials, setting, methods: Inclusion criteria were: female patients with confirmed non metastatic breast cancer, 18 to 40 years of age, with indication of neoadjuvant chemotherapy, who have had oocyte retrieval for FP after COH or IVM +/- cryopreservation of ovarian tissue. Various time-points related to cancer diagnosis, FP or chemotherapy were obtained from medical record review. Main results and the role of chance: A total of 198 patients with confirmed breast cancer who had oocyte retrieval following COH (n = 57) or IVM +/- cryopreservation of ovarian tissue (n = 141) for FP prior to neoadjuvant chemotherapy were included. Although women in IVM group were significantly younger as compared to patients who underwent COH (31.7 ± 4.2 vs. 33.3 ± 4.0 years, p = 0.019), ovarian reserve parameters, BMI and cancer stage did not differ between the two groups. Overall, the average time from cancer diagnosis to chemotherapy start was similar between patients having undergone COH or IVM before oocyte vitrification (37.3 ± 13.8 vs. 36.9 ±13.5 days in COH and IVM groups respectively,  p=0.857). Limitations, reasons for caution: The time from referral to FP consultation may have influenced the type of FP. In addition, the retrospective nature of the present analysis may constitute a limitation. Moreover, the efficiency and security of the different FP strategies used has not been analysed. Wider implications of the findings: Oocyte vitrification following COH or IVM was not associated with delayed breast cancer treatment in the neoadjuvant setting, so long as there was a prompt FP referral. Young patients undergoing neoadjuvant chemotherapy should be informed of these findings to avoid unnecessary anxiety due to concern for delays. Trial registration number: Not applicable